Low Level of Perfectionism as a Possible Risk Factor for Suicide in Adolescents With Attention-Deficit/Hyperactivity Disorder - Katzenmajer-Pump, Luca; Farkas, Bernadett Frida; Varga, Balázs András; Jansma, Johan M.; Balázs, Judit (Frontiers in Psychiatry, 2021)
Introduction: Suicide is one of the leading causes of death among adolescents. Although it is known that both perfectionism and attention-deficit/hyperactivity disorder (‘ADHD’) are important risk factors for suicide, there are no studies that have investigated the relationship between suicidal behavior and perfectionism among people with ADHD. Aim: The current study investigates the association between perfectionism and suicide in adolescents with ADHD. Method: Subjects included 88 adolescents with ADHD and 96 non-clinical control adolescents. We used the Multidimensional Perfectionism Scale to evaluate perfectionism as well as its separate traits, and the Mini International Neuropsychologic Interview Kid to evaluate psychiatric disorders and suicidal behavior. Differences between the groups were statistically evaluated using t-tests, a Poisson regression analysis with suicide as a discrete variable, and a logistic regression analysis with suicide as a binary variable. Results: Compared to the control group, the ADHD group showed a significantly lower level on the adaptive ‘Organization’ trait of perfectionism, but not on any other trait, and a significantly higher level of suicidal behavior. Logistic regression results indicated a significant association for perfectionism in general (OR = 0.93, p = 0.003), and for the ‘Personal Standards’ trait (OR: 0.82, p = 0.039). Poisson regression analysis also showed a significant association with perfectionism in general (IRR = 0.90; p < 0.001) and with the ‘Personal standards’ trait model (IRR = 0.81, p = 0.019). Discussion: Our results indicate that a low level of perfectionism, in particular ‘Personal standards’, may be a risk factor for suicidal behavior in adolescents with ADHD. We recommend that psychoeducation and therapy of adolescents with ADHD should consider focusing on adaptive perfection as a possible risk factor for suicide as well.